THE GEOGRAPHY OF CRIME AND ITS SOCIAL ASPECTS - Gonçalves, Luis Fernando (Seven Editora, 2025)
This study analyzes the complex relationship between urban space and crime in Brazil, proposing a multidisciplinary approach that integrates territorial planning, sociology, and psychoanalysis. Initially, the text addresses Geographic Criminology, which shifts the focus of analysis from individual "moral failure" to the "vulnerability of place." Through the concept of "opaque spaces," areas characterized by precarious infrastructure and low surveillance, it demonstrates that crime is not a random phenomenon, but a response to urban anomalies and opportunities generated by daily routine. Empirical data corroborate this thesis, indicating that offenders tend to operate in their "familiar space," with a significant portion of crimes occurring within a radius of less than 3 km from their residence. In the sociological context, the text establishes a correlation between crime and the lack of basic opportunities, such as education and leisure, in the peripheries. This text criticizes the stigmatization of the "marginalized" population, arguing that social marginality is a construct resulting from disordered urban growth and the absence of universal public policies. The analysis delves into Critical Criminology, denouncing the transition from the Welfare State to a "Penal State" under neoliberal logic. According to this perspective, the penal system acts as a selective mechanism for stigmatizing vulnerable populations, functioning as an instrument of social control in service of capital accumulation. In the sociological context, the text establishes a correlation between crime and the lack of basic opportunities, such as education and leisure, in the peripheries. According to this perspective, the penal system acts as a selective mechanism for stigmatizing vulnerable populations, functioning as an instrument of social control in service of capital accumulation. DOI: https://doi.org/10.56238/sevened2025.040-010